Learning foundation for the cursed equilibrium - Topi Miettinen (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
Recent literature has questioned the existence of a learning foundation for the partially cursed equilibrium. This paper closes the gap by showing that a partially cursed equilibrium corresponds to a particular analogy-based expectation equilibrium.
Keywords: C72; D82; 330; Analogy expectations; bounded rationality; curse; learning; Nash-Gleichgewicht; Spieltheorie; Unvollkommene Information; Lernprozess; Beschränkte Rationalität; Theorie